Era uma Vez um Homem e o Seu Tempo: Relações de Identidade, Memória E melancolia de Resistência em Belchior - Gabriel, Camila Teixeira (2020)
This dissertation aims to investigate the relationships between the concepts of identity, memory and resistance melancholy in the literomusical discourse of the singer and composer, Belchior. It is considered that the work of this cearense artist highligh